Fifteen-minute consultation: Neonatal hypertension. Issue 1 (19th November 2020) - Singh, Yogen; McGeoch, Luke; Job, Sajeev
Abstract : Neonatal hypertension is a rare but well recognised condition, especially in newborns needing invasive monitoring in the intensive care unit. Recognition of newborns with hypertension remains challenging because of natural variability in blood pressure with postconceptional age and the lack of reference data for different gestational ages. Investigation of neonates with hypertension can be challenging in light of the myriad differing aetiologies. This may be simplified by a systematic approach to investigation. There remains a relative paucity of data to guide the use of pharmacological therapies for hypertension in neonates. Clinicians rely on empirical management protocols based on experience and expert opinion. Much of the information on dosing regimens and protocols has simply been derived from the use of antihypertensive agents in older children and in adults, despite fundamental pathophysiological differences.